If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 2u = -7 Solving -5 + 2u = -7 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2u = -7 + 5 Combine like terms: -5 + 5 = 0 0 + 2u = -7 + 5 2u = -7 + 5 Combine like terms: -7 + 5 = -2 2u = -2 Divide each side by '2'. u = -1 Simplifying u = -1
| 3n+75=50+2n | | -(-7+4x)=8x+18 | | 19=3+4v | | 6-6x=-12-4x | | 180=(3x+y-10)+x+5 | | 180=3x+y-10+x+5 | | N-25=5 | | x+6+x+9+x+3=180 | | -7=3w-4 | | 11x-12=6x-2 | | 15b^2+10b-8= | | 3(n-6)=8+4n | | .75x+8=x | | 0=x*2-x-30 | | -6=y+3 | | 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 |